2017
DOI: 10.1371/journal.pone.0177661
|View full text |Cite
|
Sign up to set email alerts
|

MiR-338-3p regulates neuronal maturation and suppresses glioblastoma proliferation

Abstract: Neurogenesis is a highly-regulated process occurring in the dentate gyrus that has been linked to learning, memory, and antidepressant efficacy. MicroRNAs (miRNAs) have been previously shown to play an important role in the regulation of neuronal development and neurogenesis in the dentate gyrus via modulation of gene expression. However, this mode of regulation is both incompletely described in the literature thus far and highly multifactorial. In this study, we designed sensors and detected relative levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 54 publications
(59 reference statements)
1
25
0
Order By: Relevance
“…miR-338-3p has been reported to be involved in the progression and development of various types of cancer (9)(10)(11)(12)(13)(14)17,18,21). However the cellular function of miR-338-3and its molecular mechanism in CRC remains unknown.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…miR-338-3p has been reported to be involved in the progression and development of various types of cancer (9)(10)(11)(12)(13)(14)17,18,21). However the cellular function of miR-338-3and its molecular mechanism in CRC remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are regulators of gene expression, which affect cell proliferation, differentiation and death (7,8). miR-338-3p is located on chromosome 17q25.3 within the 8th intron of the apoptosis-associated tyrosine kinase gene, which produces two forms: miR-338-3p and miR-338-5p (9)(10)(11)(12)(13)(14). It has been reported that chromosome 17q23-25 is a region associated with mutations in several malignant tumors (15,16).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its role as a functional miRNA in controlling different molecular pathways has been reported. miR-338-3p is involved in neuronal proliferation, maturation and neurite outgrowth and in organization in the dentate gyrus, while also acting as a tumor suppressor in vivo [134][135][136][137]. miR-338-3p is also expressed in spinal cord oligodendrocytes, where it positively regulates oligodendrocyte differentiation from precursors into mature oligodendrocytes by repressing Sox5 and Hes6, two maturation-and differentiation-inhibiting transcription factors [138,139].…”
Section: The Most Promising Potential Circulating Mirna Biomarkers Anmentioning
confidence: 99%
“…miR-338-3p exerts a regulatory effect during the proliferation and development of DG neurons. With the maturation of DG neurons, the expression of miR-338-3p increases gradually and eventually reaches a peak in the NeuN + mature neurons (94). The knockdown of miR-338-3p results in decreased dendritic branching, abnormal distribution, and increased length of dendritic spines in the hippocampal neurons, leading to the abnormal proliferation of hippocampal cells and tumorigenesis (94).…”
Section: Epigenetic Modifications In Hippocampal Developmentmentioning
confidence: 99%